2011
DOI: 10.1016/j.ajhg.2011.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Altering the miR-184 Seed Region Causes Familial Keratoconus with Cataract

Abstract: MicroRNAs (miRNAs) bind to complementary sequences within the 3' untranslated region (UTR) of mRNAs from hundreds of target genes, leading either to mRNA degradation or suppression of translation. We found that a mutation in the seed region of miR-184 (MIR184) is responsible for familial severe keratoconus combined with early-onset anterior polar cataract by deep sequencing of a linkage region known to contain the mutation. The mutant form fails to compete with miR-205 (MIR205) for overlapping target sites on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
237
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(239 citation statements)
references
References 27 publications
1
237
0
1
Order By: Relevance
“…It has been observed that some variants might be more penetrant or have a larger effect because familial aggregation of disease is observed. 10,11 While locus heterogeneity makes it difficult to identify factors unambiguously influencing the KTCN phenotype, the replication for any particular gene is expected to be rare.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that some variants might be more penetrant or have a larger effect because familial aggregation of disease is observed. 10,11 While locus heterogeneity makes it difficult to identify factors unambiguously influencing the KTCN phenotype, the replication for any particular gene is expected to be rare.…”
Section: Introductionmentioning
confidence: 99%
“…47 Concordance is also high among monozygotic twins and a greater similarity of phenotype is observed in monozygotic twin pairs implying that genetic factors are likely to have a key role in the disease phenotype. 48 KC has been associated with a wide range of systemic and ocular conditions, for example Leber congenital amaurosis, 49 anterior polar cataract, 50 Brittle cornea syndrome, 51,52 and with a 10-300-fold higher prevalence in individuals with Down syndrome. 53,54 Interestingly, individuals with connective tissue disorders such as Ehlers Danlos syndrome have a higher prevalence of KC.…”
Section: Geneticsmentioning
confidence: 99%
“…81 Of particular relevance, linkage analysis in combination with nextgeneration sequencing identified a heterozygous mutation in mir-184 in two families with dominant congenital cataract associated with a corneal phenotype that in some cases was consistent with KC. 50,82,83 To establish whether mutations in mir-184 were associated with KC, mir-184 was subsequently screened in a cohort of 780 KC patients. 84 Rare variants were identified in two (0.25%) patients, but the variants did not fully segregate with disease, suggesting that mir-184 variants are not a common cause of isolated KC.…”
Section: Geneticsmentioning
confidence: 99%
“…Genome-wide linkage analysis of affected pedigrees has shown evidence of disease susceptibility genes mapping to several putative chromosomal loci. [48][49][50][51] …”
Section: Genetic Locimentioning
confidence: 99%